Dual Effects of Presynaptic Membrane Mimetics on α-Synuclein Amyloid Aggregation - Lin, Yuxi; Ito, Dai; Yoo, Je Min; Lim, Mi Hee; Yu, Wookyung; Kawata, Yasushi; Lee, Young-Ho (Frontiers in Cell and Developmental Biology, 2022)
Aggregation of intrinsically disordered α-synuclein (αSN) under various conditions is closely related to synucleinopathies. Although various biological membranes have shown to alter the structure and aggregation propensity of αSN, a thorough understanding of the molecular and mechanical mechanism of amyloidogenesis in membranes remains unanswered. Herein, we examined the structural changes, binding properties, and amyloidogenicity of three variations of αSN mutants under two types of liposomes, 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and presynaptic vesicle mimetic (Mimic) membranes. While neutrally charged DOPC membranes elicited marginal changes in the structure and amyloid fibrillation of αSNs, negatively charged Mimic membranes induced dramatic helical folding and biphasic amyloid generation. At low concentration of Mimic membranes, the amyloid fibrillation of αSNs was promoted in a dose-dependent manner. However, further increases in the concentration constrained the fibrillation process. These results suggest the dual effect of Mimic membranes on regulating the amyloidogenesis of αSN, which is rationalized by the amyloidogenic structure of αSN and condensation-dilution of local αSN concentration. Finally, we propose physicochemical properties of αSN and membrane surfaces, and their propensity to drive electrostatic interactions as decisive factors of amyloidogenesis.